1993
DOI: 10.1063/1.110552
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electro-optic properties of pulsed laser deposited Bi4Ti3O12 thin films on MgO

Abstract: Ferroelectric Bi4Ti3O12 thin films have been grown on MgO (100) and MgO(110) substrates by the pulsed laser deposition. X-ray diffraction studies show that the films on both substrates have preferential crystallographic orientation such that most of their c axes are close to the substrate normal direction. The film on MgO(110) shows quadratic and hysteretic electro-optic characteristics with the effective coefficient of about 3.8×10−15 m2/V2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…[2] Recently, it was shown that ferroelectric Bi 4 Ti 3 O 12 thin films can find an application in electrooptic devices. [9] Another intriguing aspect of this material is its relation to high-T c oxide superconductors. As has been recently found, [10,11] one of the phases of the Bi-Ca-Sr-Cu-O oxide superconductors family with T c ∼80 K has a structure analogous to that of Bi 4 Ti 3 O 12 .…”
mentioning
confidence: 99%
“…[2] Recently, it was shown that ferroelectric Bi 4 Ti 3 O 12 thin films can find an application in electrooptic devices. [9] Another intriguing aspect of this material is its relation to high-T c oxide superconductors. As has been recently found, [10,11] one of the phases of the Bi-Ca-Sr-Cu-O oxide superconductors family with T c ∼80 K has a structure analogous to that of Bi 4 Ti 3 O 12 .…”
mentioning
confidence: 99%
“…Ternary bismuth compounds form a variety of phases such as Bi 2 SiO 5 , Bi 4 TiO 20 . These phases have been deposited by both chemical and physical methods [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, Bi 2 SiO 5 has attracted interest as buffer layer for metalferroelectric-insulator-semiconductor (MIS) structures [1,22].…”
Section: Introductionmentioning
confidence: 99%
“…Bi 12 SiO 20 (sillenite) and Bi 12 TiO 20 are both optically active materials and have been reported to be potential material choices for electro-optics [10,23,24]. Bi 4 Ti 3 O 12 is a typical ferroelectric material and it has therefore been studied for nonvolatile memories [19,25] and electro-optic devices [17]. Recently Bi 4 Ti 3 O 12 has been studied as a base material for ferroelectric memories where thin film properties were modified by incorporating a suitable rare earth cation into the Bi 4 Ti 3 O 12 lattice [26].…”
Section: Introductionmentioning
confidence: 99%
“…As a typical perovskite layered structure ferroelectric materials, bismuth titanate (Bi 4 Ti 3 O 12 (BTO)) has become a key candidate for memory storage capacitor, optical display and electrooptical devices owing to their promising ferroelectric and electro-optic properties [1][2][3][4]. Metalferroelectric-semiconductor (MFS) hetero-structure with BTO as a gate electrode material for ferroelectric field effect transistor (FFET) in a non-destructive readout (NDRO) mode has been demonstrated [5].…”
Section: Introductionmentioning
confidence: 99%